O tempora, o mores! Can We Assume That Moral Progress Exist? - Chyrowicz, Barbara (Roczniki Filozoficzne, 2025)
The idea of moral progress discussed in contemporary ethics is not interpreted unambiguously. Moral progress is supposed to be made most generally when the next state of affairs is better than the previous one, or when right actions become more and more common. Narrowly understood, moral progress refers to the improvement of morality as such, while understood broadly it has to do with changes that are desirable from a moral point of view, but do not have a direct impact on morality. Moral progress is defined as both an increase in moral knowledge and a noticeable, practical increase in respect for human rights. Authors defending the idea of moral progress see its (progress) basis in man’s discernment of moral truth (Markus, Nagel) or socio-cultural evolution (Buchanan and Powell, Fischer, Sauer). The idea of moral progress has its supporters and opponents. The latter point to the ambivalence of changes in moral customs and practices observed in various communities, which do not always go in the direction desired by the defenders of the moral order. The answer to the question of whether moral progress can be assumed to exist – this is the basic problem of the analyses conducted in the article – requires indicating the criteria that would decide about it. The article analyzes both the criteria of progress that have been present in the literature on the subject for some time, as well as new proposals for verifying moral progress, with particular reference to the concept of Thomas Nagel. Basically, all the authors mentioned in the article admit that local progress locally is possible, as is regression. The last part of the article will point out the possible reasons that make moral progress slow, with regression occurring alongside progression.